2008
DOI: 10.1590/s0103-84782008000400040
|View full text |Cite
|
Sign up to set email alerts
|

Otimização de protocolo para micropropagação da figueira "Roxo de Valinhos"

Abstract: Foram avaliados os efeitos de alterações na concentração de sacarose, do meio WPM - Wood Plant Medium - e da variação no número de gemas por segmento com diferentes doses de cinetina. Os experimentos foram conduzidos no Laboratório de Cultura de Tecidos da Universidade Federal de Lavras, utilizando plântulas previamente estabelecidas in vitro, seguindo o delineamento experimental inteiramente casualizado, em esquema fatorial 5 x 4. Os resultados mostraram que, na multiplicação de brotações de figueira "Roxo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In order to achieve greater savings in the use of salts to prepare the culture media, Fraguás (2003) tested different concentrations of the WPM medium (50, 100 and 200%) in the micropropagation of the 'Roxo de Valinhos' cultivar, and concluded that the standard WPM concentration (100%) was the most efficient for the development of explants. Ferreira and Pasqual (2008) sought to optimize the micropropagation protocol of 'Roxo de Valinhos' fig tree cultivar and also recommended the use of WPM culture medium without addition of kinetin and segments with one or two buds for the production of shoots.…”
Section: Tissue Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve greater savings in the use of salts to prepare the culture media, Fraguás (2003) tested different concentrations of the WPM medium (50, 100 and 200%) in the micropropagation of the 'Roxo de Valinhos' cultivar, and concluded that the standard WPM concentration (100%) was the most efficient for the development of explants. Ferreira and Pasqual (2008) sought to optimize the micropropagation protocol of 'Roxo de Valinhos' fig tree cultivar and also recommended the use of WPM culture medium without addition of kinetin and segments with one or two buds for the production of shoots.…”
Section: Tissue Culturementioning
confidence: 99%
“…Rocha et al (2009) attributed the development of new sprouts possibly to the increase of cytokinin concentration, as it is responsible for cell division. Thus, Ferreira and Pasqual (2008) and Fraguás et al (2004) indicated that, in order to obtain a larger number of larger and well-formed shoots, 0.5 mg L -1 of the regulator should be added to the WPM medium, using segments with three buds.…”
Section: Tissue Culturementioning
confidence: 99%